Code-switching alone cannot explain intraspeaker syntactic variability: Evidence from a spoken elicitation experiment - Lundquist, Bjørn; Westendorp, Maud; Strand, Bror-Magnus S. (Nordic Journal of Linguistics, 2020)
We address the question whether speakers activate different grammars when they encounter linguistic input from different registers, here written standardised language and spoken dialect. This question feeds into the larger theoretical and empirical question if variable syntactic patterns should be modelled as switching between different registers/grammars, or as underspecified mappings from form to meaning within one grammar. We analyse 6000 observations from 26 high school students from Tromsø, comprising more than 20 phonological, morphological, lexical and syntactic variables obtained from two elicited production experiments: one using standardised written language and one using spoken dialect as the elicitation source. The results suggest that most participants directly activate morphophonological forms from the local dialect when encountering standardised orthographic forms, suggesting that they do not treat the written and spoken language as different grammars. Furthermore, the syntactic variation does not track the morphophonological variation, which suggests that code/register-switching alone cannot explain syntactic optionality.